PENERAPAN METODE INVESTIGASI KELOMPOK PADA POKOK BAHASAN SISTEM PERSAMAAN LINIER DUA VARIABEL DENGAN MENGGUNAKAN GEOGEBRA DI KELAS VIII SMP KEMALA BHAYANGKARI 1 MEDAN - Awaludin Fitra (Universitas Quality, 2018)
Research conducted in SMP Kemala Bhayangkari 1 Medan aims to find out whether the application of Group Investigation Methods using GoeGebra can improve student learning outcomes on the subject of two-variable linear equation system (SPLDV) in grade VIII SMP Kemala Bhayangkari 1 Medan.This type of research is a quasi-experimental research, where from two classes selected as a sample that is class VIIIA as experimental class and class VIIIB as control.From the data analysis, it was found that the data of both groups were normal distribution and the two groups were homogeneous samples, before the data were obtained before the test was done by t test. From the results of statistical calculations t with a significant level α = 0.05 obtained tcount = 3.43. Furthermore tcount is consulted with ttable with dk = 78 obtained ttable = 1,994 turns thitung> ttabel this means H0 rejected and Ha accepted so that it can be concluded that from the calculation results can be known there is a significantdifference between student learning outcomes taught by Group Investigation ModelLearning using GeoGebra and Conventional learning. on the subject of the Two-VariableLinear Equation System in class VIII SMP Kemala Bhayangkari 1 Medan.